Vienuolynų ir bažnyčių bibliotekos Lietuvoje (iki 1800 m.) - Vladimirovas, Levas (Knygotyra, 1970)
Formation and development of the church and monastic libraries is of interest to a historian of culture not so much for the role of these libraries in the intellectual development of the country, as this role, even during the period of flourishing of the libraries of this type, was rather limited, but rather for these book collections, established in the course of centuries, which contained a great many valuable book material of local bibliophiles and which have transferred these collections to the following generations. The study of the history of the libraries and collections of this type, which have enriched the repositories of old books of Lithuania’s research libraries, gives a lot of valuable material about the ideological struggle in the feudal society, about the dissemination of books in the society and about the organization of library work of the period.The author is confining his study to the libraries of Catholic monastic orders, excluding the libraries of academies and colleges even though these two types were also under the authority of these orders.It is well known that during the Middle Ages monasteries were considered as centres of religious culture. But in Lithuania monasteries were being built in the time when the monastic orders, as the whole Catholic Church, went through a period of decline and degradation; as to Bishop Richard de Bury, it was a time when „in draining cups and not in mending books the study of our monks is busied today.“Extremely low level of intelectual culture was the characteristic of the Lithuania’s catholic monasteries at that period; their libraries in the 15th and 16th centuries were neither distinguished for the resources of their book collections nor for the rational organization of their work. The deterioration of the Catholic monasteries and consequently of their libraries took place during the time of the spread of Reformation in Lithuania.Due to the shift of a considerable part of the Lithuanian nobility from Catholicism to the camp of Reformation, the monasteries lost their main sponsors and patrons. Used to a parasitic way of life, idle monks began squandering the monastery treasures, including the books of the libraries.The situation of the monastic libraries somewhat improved during the time of CounterReformation and particularly in connection with the General Council of Trent, which paid due attention to the task of improving monastic libraries, without which the ideologic struggle against the “heresies” of reformation would be impossible.Thanks to the generous gifts of the magnates the network of cloisters and other monastic institutions began to grow very fast from the beginning of the 17th century. At the beginning of the 19th century, in the territory of the North-western region of the Russian Empire (comprising Lithuania and Byelorussia) there were 358 acting cloisters, with libraries having book collections of about 250,000 volumes. Among the richest of the cloister libraries in Lithuania during that time were the libraries of the Dominican cloisters in Grodno (15,000 vol.) and in Vilnius (5,000 vol.) of the Missionaries in Vilnius (8,300), and four other cloisters in the same city, the Bernardines (7,000), Piarists (7,000), Basilians (5,000) and Franciscans (5,000). Among the larger provincial cloister libraries were the Franciscan cloister in Valkininkai (4,600) and the Carmelite cloister in Glubokoe (3,000). Bernardine cloisters in Kretinga and Tituvėnai were rich in incunabula and paleotypes. The nunnery of the ord of Visitation in Vilnius (1,000 vol.) was the on one worth mentioning among the nunneries. The main source of forming the monastic collection were book gifts. Rarely would a cloister use in funds for this purpose.The analysis of the monastic collection which have reached us, the inventories and catalogue of the monastic libraries, showed that no less than eighty per cent of those collections was religious, scholastic or polemic literature. With the aristocratic gifts, the monasteries also collected some scientific literature and antique classic. Each monastery library possessed an “Index librorum prohibitorum”, but in spite of this, man of these libraries had collections of heretical books. The existence of these books in monaster libraries may be explained by the need of having these books 10 light the “apostates.”In the 16th and in the first half of the 17th centuries, these collections were prevalently in Latin, but towards the end of the 11th century Polish and the West-European languages began to increase. There were also books in Lithuanian the language of the common folk, but in very small number.Only the libraries of the larger cloisters had buildings specially for this purpose. For the majority of cloisters the libraries were situated on the second floor of the quadrilateral cloister building. Small cloisters having scanty collection of books usually housed them in the cells of the guardian, vicar, lecturer, or preacher.In the regulations of the monastic orders the functions of the librarian were defined in details he had to look after the acquisition of new books to make the books available to the members of the monastic community on terms established by the regulations, to register books which he gave on loan, to set up catalogues, to care for the safety of the collections and to keep them clean. Small libraries did not have a librarian, so the duties were mostly performed by the preacher.Books on the shelves of a cloister library were arranged by “faculties” and size. In the beginning the catalogues were nothing more than primitive inventories of literature; only in the 18th century there appeared the more complex catalogues in which book items were arranged by subject divisions and subdivisions, and within the subdivisions in alphabetical order. It must be said that books in 18th-century catalogues were described more fully and exactly than in the catalogue inventories of the 16th or the 17th centuries.In spite of the strict regulations forbidding the loan or gift of monastery books to outsiders, or even transfer of books to other cloisters, the books of the monastic libraries had the trait of migrating from one library to another. Another formidable foe of the libraries were the frequent fires and pillages during the devastating wars of the 17th and 18th centuries.The church libraries of the late feudal period are of little interest to historians. An exception to this would be the library of the Vilnius Cathedral. its book inventories was discovered by the author of this paper among the manuscripts collection of the Vilnius University and of the Historical Archives of the Lithuanian S.S.R.The majority of the bourgeois historians contended that the liquidation of the network of cloisters in Lithuania was due to the Tsarist repression. which resulted in the closing down of Catholic cloisters in the North-western region after the uprisings of 1830–31 and 1863. But the process of contraction of the cloister network and of the decrease of the role of monastic orders originated far earlier, in the second half of the 18th century; the omen of this crisis was when the Pope was forced to close the Jesuit order in 1772. In Lithuania, with the rise of the capitalist system and the development of science and education, the monastic school and library became mere anachronism, completely forfeited their importance in the intellectual life of the country. Thus, the transfer in 1865 of the cloister collections to the Vilnius Public Library (now University Library) was a progressive act. For the first time in the history of these book collections they were being released from the monasteries and became accessible to research.